Cyberbullying victimization and suicidal ideation among college students: the mediating role of psychological pain and the moderating role of school bonding - Xiufang Liu; Xiaowen Liu (BMC Psychiatry)
Abstract Background Cyberbullying victimization (CV) among college students has become an increasing serious issue in recent years, raising widespread concern. CV can result in a series of negative consequences in college students, at worst, leading to suicide. Therefore, it is crucial to better understand the mechanisms underlying the link between CV and suicidal ideation (SI). The aim of this study was to explore the mediating role of psychological pain (PP) between CV and SI, as well as the moderating role of school bonding (SB) in this mediation. Methods A cross-sectional survey was conducted among a sample of 1,247 Chinese college students aged 17 to 25 years (M = 19.98, SD = 1.57; 41.38% male, 58.62% female) in Guizhou Province. The survey utilized validated questionnaires, including the European Cyberbullying Intervention Project Questionnaire, the Positive and Negative Suicidal Ideation Scale, the Psychache Scale, and the School Connectedness Scale. SPSS 25.0 was used for the descriptive statistics and correlation analysis, and the mediated model was tested. Results CV was directly related to SI, with PP playing a partial mediating role in this relationship. SB was found to moderate both first and second halves of the mediating pathway. Conclusion PP plays a mediating role between CV and SI. SB moderates the indirect effects of CV on SI. These findings shed light on a potential mechanism of the relationship between CV and SI. Furthermore, they suggest that laws and regulations should be developed or improved by the relevant government departments to provide legal means for preventing college student CV. Additionally, colleges and families should pay attention to the psychological needs of college students and be proactive about alleviating their PP. Finally, colleges and universities should provide support and programming to help college students establish a solid SB.